Media Zona Tumbuh Kembang dalam Membangun Karakter Anti Bullying Melalui Pola Asuh Otoritatif di Sekolah Dasar - Ulfa, Maria; Husniah, Wa Ode; Kosilah, Kosilah; Fadillah, Nur; Samal, Silvia Nur Aini; Koriah, Wa Ode Nikmatul (LPPM Institut Pendidikan Nusantara Global, 2025)
Bullying in schools can have an impact on students' academic performance, character development and mental health. One of the factors causing bullying behavior is the application of inappropriate parenting. Prevention efforts require a holistic approach that actively involves the school and family environment, especially building anti-bullying character from an early age by involving parenting. The purpose of the study was to develop and test the effectiveness of the growth and development zone media in building anti-bullying character through authoritative parenting in elementary schools. The study used a research and development (R&D) approaches referring to Borg & Gall with a mixed method analysis method. The research location is State Elementary School 1 Batulo, the research population in class III (three) and the research sample is students and parents / guardians of students totaling 40 students and 40 parents. The results showed that the media developed, namely the Emotion Zone, the Children's Kindness Zone, the Children's Star and the Parents' Wish Board, were well validated and effective in increasing students' moral awareness, empathy, and prosocial behavior. Statistical test results showed a significant increase between pretest and posttest results with a Z value of -3.921 and Asym. Sig. (2-tailed) of 0.000 and it is concluded that media implementation is effective in increasing students' anti-bullying behavior. Media implementation also increases parental involvement in authoritative parenting practices. This research concludes that character-based media and authoritative parenting have great potential in preventing bullying preventively and educationally.